The Likelihood of an Occult Fracture in Skeletal Surveys Obtained in Children More Than 2 Years Old With Concerns of Physical Abuse. Issue 2 (13th February 2022) - McNamara, Caitlin R.; Panigrahy, Ashok; Sheetz, Michael; Berger, Rachel P.
Abstract : Objectives: Skeletal surveys are necessary in the evaluation for physical abuse in children less than 2 years old, but when to obtain a skeletal survey in older children is less clear. Methods: A retrospective study of patients older than 2 years who underwent skeletal survey over a 3-year period after implementation of an electronic health record physical abuse order set was conducted. Data were analyzed using descriptive statistics and compared with data from a cohort before order set implementation. The radiation dose of a skeletal survey in a 5-year old was calculated using a previously published technique. Results: There were 325 skeletal surveys, a marked increase in the rate of skeletal surveys compared with before order set implementation. Less than 2% (6/325) of skeletal surveys demonstrated an occult fracture. Of the 6 patients with occult fractures, 4 were physically abused; in each case, the diagnosis of abuse was evident before the skeletal survey. The other 2 patients fell from windows. The radiation exposure was 0.34 mSv. Conclusions: The rate of occult fractures on skeletal survey is significantly lower than previously reported. This is likely because our population included all children who underwent skeletal survey and not the subset referred to a child abuse pediatrician. In addition, our data demonstrate that in children older than 2 years, skeletal surveys are unlikely to assist in making a diagnosis of physical abuse. The radiation exposure in a 5-year-old is 70% greater than in an infant, but still a dose, which represents a negligible health risk.